Measuring Cognitive Job Satisfaction - Job Attributes to be Included : A Literature Review - Sanjeev, M. A. (Prabandhan: Indian Journal of Management, 2017)
Job satisfaction is one of the most widely studied job attitudes due to its influence on organizational performance. Like any attitude, it can be seen as a tripartite construct with cognitive, affective, and conative components. Though conative components have been clearly delineated in studies, it cannot be said so about the cognitive and affective components. Researchers have measured job satisfaction levels that have included the cognitive and affective components, often mixing up the two. This paper delineated the cognitive and affective components and considered cognitive job satisfaction to be an objective assessment of the various job attributes. Affective job satisfaction, on the other hand, is considered as an overall assessment of liking towards one's job. The paper reviewed available literature to prepare an exhaustive set of job attributes to be included while studying cognitive job satisfaction. It also proposed three different approaches to decide on which job attributes are to be included while studying cognitive job satisfaction of a particular group of employees.